Gagasan Pendidikan Muhammadiyah dan NU sebagai Potret Pendidikan Islam Moderat di Indonesia - Suharto, Toto (Program Pascasarjana UIN Sunan Ampel Surabaya, 2014)
This article deals with the educational ideas of Muhammadiyah and Nahdatul Ulama as representing the portrait of moderate Islamic education in Indonesia. The problems addressed includes whether both organizations have certain moderate ideas regarding education to seed their moderate character. Using actual philosophy approach, this study reveals that educational institutions of Muhammadiyah are characterized by a special subject matter called Al-Islam dan Kemuhammadiyahan. With the concept of objective identity of Muhammadiyahâs education, this subject matter is designed to be an instrument for Muhammadiyah to seed the moderate character of its students. Meanwhile, NUâs educational institutions are characterized by subject matter called Aswaja dan Ke-NU-an. Through the concept of SNP-Plus, this institution serves as an instrument for NU to seed the character of moderate Islam. Both organizations therefore share the same ideas to strengthen a moderate Islamic education in Indonesia on the basis of their own cultural traditions.